Hydroxyl aluminium silicate clay for biohydrogen purification by pressure swing adsorption: Physical properties, adsorption isotherm, multicomponent breakthrough curve modelling, and cycle simulation. (23rd August 2018) - Kuroda, Shohei; Nagaishi, Taira; Kameyama, Mitsuo; Koido, Kenji; Seo, Yuna; Dowaki, Kiyoshi
Abstract: Hydroxyl aluminium silicate clay (HAS-Clay) is a novel adsorbent in pressure swing adsorption for CO2 capture (CO2 -PSA) and can also adsorb H2 S. To investigate the performance of HAS-Clay as a CO2 -PSA adsorbent, multicomponent breakthrough curves were determined using experimental measurements and theoretical models, and, based on those results, CO2 -PSA simulations were conducted. The breakthrough curves produced from the theoretical models agreed well with those derived from experiment. CO2 -PSA with HAS-Clay could purify biomass-gasification-derived producer gas of contaminants (carbon dioxide, methane, carbon monoxide, and hydrogen sulfide) with high CO2 recovery and low energy input. The CO2 recovery rate of CO2 -PSA with HAS-Clay was 58.4%, and the CO2 purity was 98.4%. The specific energy demand was 2.83 MJ/kg-CO2 . In addition, the H2 S regenerability of HAS-Clay was investigated. The results show that HAS-Clay retained the ability to adsorb H2 S at a steady-state value of 0.02 mol/kg for the regeneration cycles. Therefore, it is suggested that CO2 -PSA with HAS-Clay is suitable for CO2 separation from multicomponent gas mixtures. Graphical abstract: Image 1 Highlights: Performance of HAS-Clay as CO2 -PSA adsorbent is investigated. Physical properties and adsorption isotherm of HAS-Clay are experimentally clarified. Multicomponent breakthrough curves are observed, compared to theoretical models. CO2 -PSA with HAS-Clay were simulated using the theoretical models. CO2 recovery rate, CO2 purity, and specific energy demand are revealed.